(3PNjQI GdZfi hGdeMJGL aj UGMH GddhGA hGdJGLs - (3eMeO GdeYWj Hf eMeO GdUGdM GdTQbGhjs
(3ChdgG (B:s
(3GdMeO ddg GdPi CdHS ChdjGAg edGHS GdYRI s
(3BNQgG (B:s
(3hYdi Bdg hCUMGHI GdcQGe EfJgJ s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdNRGfI GdYGeI HGdQHGW (B- (3GdeZQH (B(357 D) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs